Exploring elementary school student's understanding and experience of pancasila values in using the tiktok application: a qualitative study - Sari, Laras Nopita; Sarifah, Iva; Yudha, Chrisnaji Banindra (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2024)
This research aims to explore elementary school students' understanding and experience of Pancasila values in using the TikTok application. The background to this research focuses on the increasingly dominant influence of social media in children's lives and the need to understand how Pancasila values are internalized in the digital era. The research method used is a qualitative approach with data collection techniques in the form of in-depth interviews, focus group discussions (FGD), and participatory observation. Participants in this study consisted of 30 students in grades 4 to 6 from three elementary schools in Indonesia, as well as their parents and teachers. The research results show that students have a theoretical understanding of Pancasila values, but their application in using TikTok is still limited. Students are more likely to be exposed to entertainment content than educational content that reflects Pancasila values. Parents and teachers play an important role in supervising and guiding students' use of TikTok. However, further efforts are needed to bridge the gap between understanding and practicing Pancasila values on social media. The conclusions of this research emphasize the importance of a holistic approach in teaching Pancasila values, by using social media wisely. Social Learning Theory highlights the importance of observation, imitation, and self-efficacy in this learning process. With collaboration between educators, parents and content creators, TikTok can be used as an effective tool to educate and internalize Pancasila values in students.